PENGATURAN PERSEDIAAN BERAS DI PERUM BULOG DIVRE SULTENG DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Nildawati, Nildawati; Ratianingsih, R; Sahari, A (Program Studi Matematika, Universitas Tadulako, 2018)
Perum BULOG of Central Sulawesi Division is a national rice logistic company that its responsibility is to guarantee the sufficiency to meet the rice needs. Perum BULOG also responsible to keep rice price stability. One of the rice price component is the inventory costs that need to be managed. In this research the management is refered to the rice scheme demand of four storages, that are Olaya, Lawanga, Jaya Kencana Toili and Galang. This study uses EOQ (Economic Order Quantity) that consist of five priorities, that are determining the of economical order, determining the amount of safety stock, determining the maximum inventory quantities, determining the reorder point and determining total inventory cost. The results showed that the number of economical order storage of Olaya is 1.817.120,57 kg/message, Lawanga is 1.893.400,78 kg/message, Jaya Kencana Toili is 1.575.543,38 kg/messages and Galang is 1.578.742,75 kg/message. The total Inventory Security for Olaya is 32.371,28 kg, Lawanga is 41.020,07 kg, Jaya Kencana Toili is 30.630,61 kg, and Galang is 57.307,99kg. The maximum inventory for Olaya is 1.849.491,85 kg, Lawanga is 1.934.420,85 kg, Jaya Kencana Toili is 1.606.173,99 kg, and Galang is 1.636.050,74 kg. The reorder point is proposed when rice stock of Olaya reaches 323.664,52 kg, Lawanga reaches 357.282,87 kg, Jaya Kencana Toili reaches 249.620,29 kg and Galang reaches 277.188 kg. The total inventory cost that use Economic Order Quantity is Rp. 2.507.626,39 for Olaya, Rp. 2.612.893,07 for Lawanga, Rp.2.174.249 ,87 for Jaya Kencana Toili, and Rp 2.178.665,00 for Galang. The Efficiency cost of rice supplies BULOG Division is Rp.40.405,29 for Olaya, Rp. 719.256,02 for Lawanga, Rp. 51187.63 for Jaya Kencana Toili, and Rp. 153.528,73 for Galang. These result gives greatest efficiency at the cost of supplies of Perum BULOG Division Central Sulawesi for Lawanga 22% as much.